The management and clinical outcomes of pregnancies in women with urea cycle disorders: a review of the literature and results of an international survey - Stepien, Karolina M.; Langendonk, Janneke G.; Dao, Myriam; Gomes, Daniel Costa; Douillard, Claire; Filipsson, Karin; Glamuzina, Emma; Haverkamp, Jorien A.; Langeveld, Mirjam; Lehman, Anna; de Lonlay, Pascale; Lund, Allan M.; et al. (Journal of inherited metabolic disease, 2023)
An increasing number of women with urea cycle disorders (UCDs) are reaching child-bearing age and becoming pregnant. Improved diagnostics and increased awareness of inherited metabolic diseases has also led to more previously undetected women being diagnosed with a UCD during or shortly after pregnancy. Pregnancy increases the risk of acute metabolic decompensation with hyperammonemia—which can occur in any trimester, and/or the postpartum period, and may lead to encephalopathy, psychosis, coma, and even death, if not diagnosed promptly and treated appropriately. There are also (theoretical) concerns that a maternal UCD, or its treatment, may cause potential risks for the unborn child. Currently evidence on management and outcome of pregnancies in UCDs is limited to case reports and there are no clear guidelines. In order to inform management and investigate outcomes of pregnancies in women with a UCD, we performed a retrospective review of published cases and analyzed data collected from an international online survey. We conclude that, although risk during the intra- and postpartum period exists, multidisciplinary management by an experienced team and a prospective plan usually result in successful pregnancy, labor, delivery, and postpartum period. No deaths were reported in mothers managed accordingly. With the exception of male neonates with Ornithine Transcarbamylase deficiency, the clinical outcome of children born to mothers with UCDs appears positive, although follow-up is limited. The outcome for women presenting with a first acute metabolic decompensation during pregnancy or postpartum is less favorable. Deaths were associated with diagnostic delay/late management of hyperammonemia in previously undiagnosed women.